The Impact of Advances in Digital Technology on Education and Students’ Moral Character - Rahmawati Adi Kurnia Dewi; Binta Laa Roiba; Muhammad Akhsan Abdillah; Alma Faizsani Maula El Imany; Vini Andini; Pandu Budi Aji; Irmas Ruhatul Zakiah; Arif Widagdo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital technological advancement has transformed contemporary educational systems by reshaping learning processes, expanding access to information, and influencing students’ moral development. This study aims to examine the impacts of digital technology on education and students’ moral character while identifying strategies for balancing educational innovation with ethical development. The research employed a non-empirical qualitative design using a literature review approach. Data were derived from scholarly journals, academic books, policy documents, and relevant educational publications concerning digital technology, digital literacy, character education, and student development. The findings indicate that digital technology contributes positively to educational effectiveness through increased learning accessibility, learner autonomy, motivation, collaboration, and pedagogical innovation. Simultaneously, technological exposure presents challenges related to academic integrity, digital dependency, cyberbullying, reduced interpersonal sensitivity, and moral degradation. The analysis further reveals that positive educational and moral outcomes depend on the integration of character education, digital literacy, family guidance, supportive school culture, and coherent educational policies. The study concludes that sustainable digital transformation in education requires a balanced framework that harmonizes technological advancement with ethical values, enabling students to become digitally competent, socially responsible, and morally grounded individuals in the digital era.